Lift every voice : African American oratory, 1787-1900 - Foner, Philip Sheldon, 1910-1994; Branham, Robert J. (Studies in rhetoric and communication., 1998)
"Oratory has played a vital role in struggles for liberation and social reform throughout U.S. history. Containing more than 150 speeches, this volume represents the most extensive and diverse collection of African American oratory of the 18th and 19th centuries ever published."--Jacket